(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Patients with schizophrenia are commonly found to be non-adherent and non-satisfied with the medication for different reasons. This study aims to determine the effectiveness of adherence therapy, based on techniques of cognitive behavioral therapy and motivational interviewing, on satisfaction and medication adherence among patients with schizophrenia. Patients and methods: The study was conducted in Psychiatry Department Sir Ganga Ram Hospital, from March to December 2021. The schizophrenia patients were diagnosed according to Diagnostic and Statistical Manual-5 criteria from the outpatient Department . Patients who were non-adherent as assessed by Drug Attitude Inventory-10 (score <0) and not satisfied on Patient Satisfaction Questionnaire-18 (score <54) respectively before initiating the study were enrolled and divided randomly into two equal groups of 31 patients each. Baseline DAI-10 and PSQ-18 scores were noted down. Patients in Group A underwent adherence therapy on a weekly basis for six consecutive weeks. In Group B (control group), the standard of care was given (antipsychotics along with psychoeducation) at six weeks, PSQ-18 and DAI-10 scale scores were again noted down and compared for the effectiveness of both interventions were compared by independent t-test, and a p-value of ≤0.05 indicated a difference in effectiveness between both groups. Results: 48.4% of males and 51.6% of females participated in the study. The mean age in Groups A and B was 27 6.07 and 28 6.84 years. The mean DAI-10 score at baseline was -4 2.27 and -3 2.21 and at 6 weeks was 3 3.44 and 0 2.37 (p=0.006), respectively. The mean PSQ-18 score at baseline in Group A vs. B was 37 8.75 and 36 8.62 and at 6 weeks, was 67 13.81 and 43 9.1 respectively (p=0.012). Conclusion: Adherence therapy was more effective than the standard of care in improving patient satisfaction and medication adherence among patients with schizophrenia